2021
DOI: 10.1038/s41598-021-00430-3
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB regulation in maternal immunity during normal and IUGR pregnancies

Abstract: Intrauterine Growth Restriction (IUGR) is a leading cause of perinatal death with no effective cure, affecting 5–10% pregnancies globally. Suppressed pro-inflammatory Th1/Th17 immunity is necessary for pregnancy success. However, in IUGR, the inflammatory response is enhanced and there is a limited understanding of the mechanisms that lead to this abnormality. Regulation of maternal T-cells during pregnancy is driven by Nuclear Factor Kappa B p65 (NF-κB p65), and we have previously shown that p65 degradation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Data regarding immune‐mediated mechanisms and the role of EVs in pregnancies complicated by fetal growth restriction without preeclampsia are scant. Isolated sEVs from the plasma of women with fetal growth restriction exhibit reduced levels of sEVs that carry Fas‐L, leading to less T cell suppression, as observed in normal pregnancy 229 . In women with fetal growth restriction, we found no change in the number or size of maternal plasma sEVs or their miRNA cargo 217 …”
Section: Evs' Modulated Immunity In Gestational Diseasesmentioning
confidence: 55%
See 1 more Smart Citation
“…Data regarding immune‐mediated mechanisms and the role of EVs in pregnancies complicated by fetal growth restriction without preeclampsia are scant. Isolated sEVs from the plasma of women with fetal growth restriction exhibit reduced levels of sEVs that carry Fas‐L, leading to less T cell suppression, as observed in normal pregnancy 229 . In women with fetal growth restriction, we found no change in the number or size of maternal plasma sEVs or their miRNA cargo 217 …”
Section: Evs' Modulated Immunity In Gestational Diseasesmentioning
confidence: 55%
“…Isolated sEVs from the plasma of women with fetal growth restriction exhibit reduced levels of sEVs that carry Fas-L, leading to less T cell suppression, as observed in normal pregnancy. 229 In women with fetal growth restriction, we found no change in the number or size of maternal plasma sEVs or their miRNA cargo. 217…”
Section: Preeclampsia and Fetal Growth Restrictionmentioning
confidence: 66%
“…3 The morphology of a placental exosomes, noting the roles of specific markers which mainly relate to immunomodulatory functions [36,47], together with cellular signalling and recognition markers [47], which include placenta-specific domains [35] involved in reproductive processes [43]. The downregulation of the T cell immune response assists with appropriate foetal recognition and by extension regulates inflammatory pathways [51].…”
Section: Exosomes In the Placental Development Processmentioning
confidence: 99%
“…For example, previous research has shown that an increase in a Th1 immune response and cytokines (TNF-α, CXCL10, and IFN-γ) has been associated with pro-inflammatory pathways and an increased incidence of adverse developmental events and miscarriages [52,53]. Hence, exosomes which carry syncytin-1 may reduce the occurrence of adverse maternal events and assist in regulating the levels of inflammation during the multiple stages of conception [50][51][52][53].…”
Section: Exosomes In the Placental Development Processmentioning
confidence: 99%
“…Alter metabolic pathways associated with GDM [172] Mediate glucose intolerance during pregnancy [173] Gestational diabetes mellitus N/A Insulin secretion and regulation; Glucose transport [173,174] Placenta Biomarkers of placental function [175] Increase inflammation in maternal uterine cells [176] Amnion epithelial cells Carry HMGB1; Induce labor [177] Group B Streptococcus Induce labor [178] Preterm birth N/A Biomarkers of preterm labor [179][180][181] Placenta Mediate maternal immune tolerance to the fetus [140,182 ] Fetal growth restriction Umbilical cord blood Reduce angiogenic properties of human umbilical vein endothelial cells [183] EVs: Extracellular vesicles; GDM: gestational diabetes mellitus. circulation [161] .…”
Section: Placentamentioning
confidence: 99%